The Relationship of Internal Control Evaluation and Audit Sample Size. - Smith, Kenneth A. (The Accounting Review, 1972)
This article presents information on the relationship between internal control evaluation and audit sample size. The purpose of this paper was to analyze the relationship of internal control and sample size and to discuss the two suggested linking techniques. There is a logical relationship between internal control and sample size and that, although either proposed technique accomplishes the linking, the Bayesian approach is preferable. A seemingly plausible and often stated justification for relating control and saw pie size is the direct effect that internal control exercises over the state of the population from which the sample is drawn. It is apparent that internal control procedures will determine the possibility of errors within a population. Good control exhibits a causal relationship diminishing probability of errors as control effectiveness decreases, the probability of errors increases. Thus, this obvious relationship seems to justify the inverse relationship of control and necessary sample size. However, although it is not readily apparent, the state of internal control and sample size are automatically linked in classical sampling theory. The confidence level and precision with which an auditor desires to make an estimate from a sample are a function of the size of the sample and the statistical variance of the population from which the sample is drawn.